2016
DOI: 10.1186/s12711-016-0266-1
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the genetic composition of South African Sanga cattle using SNP data from cattle breeds worldwide

Abstract: BackgroundUnderstanding the history of cattle breeds is important because it provides the basis for developing appropriate selection and breed improvement programs. In this study, patterns of ancestry and admixture in Afrikaner, Nguni, Drakensberger and Bonsmara cattle of South Africa were investigated. We used 50 K single nucleotide polymorphism genotypes that were previously generated for the Afrikaner (n = 36), Nguni (n = 50), Drakensberger (n = 47) and Bonsmara (n = 44) breeds, and for 394 reference animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
5
30
1
Order By: Relevance
“…However, the Mashona is genetically more distant from the Nkone compared with the Tuli. These breeds have similar evolutionary patterns, having descended from the same Ethiopian ancestral cattle (Ramsay, 2010) and then separated geographically through ethnic or tribal ownership (Rowlands et al, 2003;Makina et al, 2016). Carr et al (1966) used biochemical markers (serum transferrin type and haemoglobin loci) on indigenous cattle genotypes of Zimbabwe and Zambia (Nkone, Mashona, Tuli, Angoni and Afrikaner) and found them to be distinct breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Mashona is genetically more distant from the Nkone compared with the Tuli. These breeds have similar evolutionary patterns, having descended from the same Ethiopian ancestral cattle (Ramsay, 2010) and then separated geographically through ethnic or tribal ownership (Rowlands et al, 2003;Makina et al, 2016). Carr et al (1966) used biochemical markers (serum transferrin type and haemoglobin loci) on indigenous cattle genotypes of Zimbabwe and Zambia (Nkone, Mashona, Tuli, Angoni and Afrikaner) and found them to be distinct breeds.…”
Section: Discussionmentioning
confidence: 99%
“…In southern Africa, microsatellite markers have been used in population genetic studies of some Sanga cattle genotypes such as the Mozambican Landim (Bessa et al, 2009) and the South African Nguni (Sanarana et al, 2016). The genetic diversity of cattle has also recently been studied using SNP markers in Ethiopia (Edea et al, 2013) and South Africa (Makina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of DNA markers such as microsatellites provided the opportunity to perform population studies and contributed to knowledge of genetic diversity of farm animals, especially indigenous genetic resources (Hassen et al, 2009;Qwabe et al, 2012;Greyvenstein et al, 2016;Makina et al, 2016;Mdladla et al, 2016). In 1998 the Food and Agricultural Organisation (FAO) documented guidelines for conservation of farm animal genetic resources and listed the recommended microsatellite marker panels from the International Society for Animal Genetics (ISAG) for the evaluation of genetic diversity in farm animal species (FAO, 1998).…”
Section: Genomic Research In Farm Animalsmentioning
confidence: 99%
“…Zwane et al (2016) and Lashmar et al (2018) confirmed the tendency towards low MAF in Sanga breeds using GeneSeek®'s GGP 80K and GGP 150K bead chips, respectively. In a series of successive studies, the authors who did the original validation, investigated the genetic diversity (Makina et al, 2014;Makina et al, 2016), linkage disequilibrium (LD) and effective population size (N e ) (Makina et al, 2015a) as well as selection signatures (Makina et al, 2015b) of indigenous breeds. The SNP50 bead chip was also utilized to identify copy number variations (CNVs) in Nguni cattle (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%